Sexual Feelings Toward Clients in the Psychotherapeutic Relationship: The Taboo Revealed. (April 2021) - Vesentini, Lara; Van Puyenbroeck, Hubert; De Wachter, Dirk; Matthys, Frieda; Bilsen, Johan
Talking about sexual feelings toward clients is still difficult for many mental health professionals. This is unfortunate, because exploring and talking about these feelings with peers (especially senior ones) or supervisors can help professionals to recognize, acknowledge, accept, and handle these feelings well. This focus group study explores the various factors that contribute to psychotherapists' hesitancy to talk about these feelings. The analysis revealed two important impeding factors: the psychotherapists felt discomfortable and a safe environment was lacking. Young, less experienced psychotherapists and psychiatrists seemed to be most vulnerable. Furthermore, more profound sexual feelings were "disguised" in some cases by using a more acceptable narrative, such as " intimate feelings, " which possibly also impeded acknowledgment and discussion of these feelings. These insights might help to open up the way for psychotherapists to explore and come forward with their sexual feelings and experiences.